Development of a Web-Based TOEFL E-Certificate System with QR Code Verification and AES–SHA-256 Security Framework - Zainal Arifin (Journal of Information Systems and Technology, 2026)
The rapid advancement of digital technologies has accelerated the adoption of electronic certification systems in higher education institutions, including TOEFL certificate management. However, issues related to document authenticity, data security, and verification reliability remain significant challenges. This study aims to develop a secure web-based TOEFL electronic certificate (e-certificate) system that integrates QR code verification with cryptographic techniques, specifically the Advanced Encryption Standard (AES) and Secure Hash Algorithm 256 (SHA-256). The proposed system enables efficient certificate generation, storage, and validation while ensuring data integrity and protection against unauthorized access and forgery. QR codes are utilized to provide instant and user-friendly verification, linking each certificate to a secure database. AES encryption is applied to safeguard sensitive data, while SHA-256 hashing ensures the integrity and authenticity of certificate information. The system is developed using a structured software development approach and evaluated through functional testing and user acceptance testing. The results indicate that the proposed system significantly enhances security, reliability, and efficiency compared to conventional certificate management methods. Furthermore, it provides a scalable and practical solution for academic institutions seeking to implement secure digital certification systems.